Efek Ukuran Perusahaan, Tingkat Pertumbuhan Terhadap Struktur Modal Sub Sektor Perdagangan Eceran - Gunawan, Dessy; Meirisa, Faradila (MDP Student Conference, 2024)
This test aims to be able to understand what is being studied. The method used in this test was quantitative descriptive and the samples used were 25 from 27 companies. The findings state that company size only has an insignificant influence on capital structure, but the growth rate has a strong influence.